Experimental study on soil improvement by electrochemical injection coupled with anode movement technique - Han, Shaoyang; Yu, Daiguang; Luo, Haidong; Li, Tianyi; Wang, Yu; Zhang, Yijiang (Frontiers in Earth Science, 2024)
An improved electroosmotic method which involves coupling anode movement with injection of calcium chloride (CaCl2) solution into soils during the electroosmotic process was proposed in this paper. The laboratory-based experimental study was conducted in a custom-designed test set-up to assess the effectiveness of the proposed method. During the electroosmotic process, the drained water, drainage rate, electric current, electric resistance, power consumption, settlement, and penetration resistance were monitored. The experimental study showed that after treatment, the drainage volume was about 3.5 times that of the pure electroosmotic, 1.6 times that of the electroosmotic process with injection only, and 2.4 times that of the electroosmotic process with anode movement only. Further, electrochemical injection coupled with anode movement can significantly reduce the non-uniform electrochemical changes in the treated samples, resulting in a relatively uniform settlement and considerable cementation area throughout the sample. The results demonstrate that using this method can effectively alleviate anode corrosion, double the voltage gradient and mitigate the electric resistance increase, further enhancing electroosmotic treatment efficiency.